Survival and complications after neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy for locally advanced gastric cancer: a systematic review and meta-analysis - Zhu, Youqi; Chen, Jiuzhou; Sun, Xueqing; Lou, Yufei; Fang, Miao; Zhou, Fengjuan; Zhang, Lei; Xin, Yong (Frontiers in Oncology, 2023)
Objectives: To evaluate the efficacy and safety of neoadjuvant chemoradiotherapy(NACRT) versus neoadjuvant chemotherapy(NACT) in the treatment of locally advanced gastric cancer(LAGC). Methods: We searched Wanfang Database, China National Knowledge Network database, VIP database, China Biomedical Literature Database, PubMed, Embase and Cochrane Library. The searched terms included‘Stomach Neoplasms’, ‘Neoadjuvant Therapy’ and ‘Chemoradiotherapy’. The retrieval time was from the establishment of the corresponding database to September 2022, and our meta-analysis was performed using RevMan (version 5.3) and Stata (version 17) software. Results: A total of 17 literatures were included, which involved 7 randomized controlled trials(RCTs) and 10 retrospective studies, with a total of 6831 patients. The results of meta-analysis showed that the Complete response (CR) (RR=1.95, 95%CI 1.39-2.73, p=0.0001) of NACRT group, partial response (PR) (RR=1.44, 95%CI 1.22-1.71, p=0.0001), the objective response rate(ORR) (RR=1.37, 95%CI 1.27-1.54, p=0.00001), pathologic complete response(pCR) rate(RR=3.39, 95%CI 2.17-5.30, p=0.00001), the R0 resection rate(RR=1.18, 95%CI 1.09-1.29, p=0.0001) and 3-year overall survival(OS) (HR=0.89, 95%CI 0.82-0.96, p=0.002) were significantly improved compared with NACT group, the stable disease (SD) (RR=0.59, 95%CI:0.44-0.81, P=0.0010) of NACRT group was lower than that of NACT group, and there were no statistical significance in progressive disease (PD)(RR=0.57, 95%CI:0.31-1.03, P=0.06), five-year overall survival(OS)(HR=1.03, 95%CI:0.99-1.07, P=0.839), postoperative complications and adverse reactions between the NACRT group and NACT group. Conclusion: Compared with NACT, NACRT might bring more survival benefits without significantly increasing adverse reactions. NACRT may be a recommended treatment for patients with LAGC. Systematic Review Registration: https://inplasy.com/inplasy-2022-12-0068/, registration number INPLASY202212068.